2016
DOI: 10.18178/ijke.2016.2.3.064
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Mi-POS: Malay Part-of-Speech Tagger

Abstract: Index Terms-Benchmarking, Malay language, natural language processing, part-of-speech tagging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…However, their approach resulted in low accuracy due to incorrect mapping in language structure. The current work by Xian et al (2016) performed a benchmarking experiment on previous Malay POS approaches. Their Mi-POS used machine learning probabilistic methods for the POS tagging by referring to the training corpora.…”
Section: Malay Natural Language Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, their approach resulted in low accuracy due to incorrect mapping in language structure. The current work by Xian et al (2016) performed a benchmarking experiment on previous Malay POS approaches. Their Mi-POS used machine learning probabilistic methods for the POS tagging by referring to the training corpora.…”
Section: Malay Natural Language Processingmentioning
confidence: 99%
“…The Accuracy Results of the Mi-POS Technique Against the Existing Methods Using Two Different Testing Malay Corpora (news and nonnews) (Xian et al, 2016).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Once each token is tagged, compound phrase that are exists in the sentence will be identified. In this study, POS tagging are based on those Malay POS tagger (Mi-POS) (Xian et. Al., 2016).…”
Section: Pos Taggingmentioning
confidence: 99%
“…The reason behind unique name is because of the annotation process. This method does not require heavy process of annotating the dataset for training like other method as it annotates dataset using a Besides that, a research completed by [7]for Malay POS tagger called Mi-POS revealed to have higher accuracy at 95.16%. Mi-POS is a statistical POS tagger approaches that use a large dataset.…”
Section: Named Entity Recognitionmentioning
confidence: 99%